3D Bioprinting Pluripotent Stem Cell Derived Neural Tissues Using a Novel Fibrin Bioink Containing Drug Releasing Microspheres - Sharma, Ruchi; Smits, Imke P. M.; De La Vega, Laura; Lee, Christopher; Willerth, Stephanie M. (Frontiers in Bioengineering and Biotechnology, 2020)
3D bioprinting combines cells with a supportive bioink to fabricate multiscale, multi-cellular structures that imitate native tissues. Here, we demonstrate how our novel fibrin-based bioink formulation combined with drug releasing microspheres can serve as a tool for bioprinting tissues using human induced pluripotent stem cell (hiPSC)-derived neural progenitor cells (NPCs). Microspheres, small spherical particles, can provide a controlled release rate for drugs like guggulsterone, shown to promote hiPSC differentiation into dopaminergic neurons, making them a valuable tool for tissue engineering. We printed dome shaped structures with a 1 cm diameter using the Aspect Biosystems RX1 bioprinter with our novel bioink consisting of fibrin, alginate and genipin containing guggulsterone microspheres crosslinked by a mixture of calcium chloride, chitosan and thrombin. Cell viability one day post printing was over 90% for the cells printed using our bioink containing guggulsterone microspheres that increased to 95%, 7 days after printing. The bioprinted tissues expressed the early neuronal marker, TUJ1 and the early midbrain marker, forkhead/winged helix transcription factor (FOXA2) (Forkhead Box A2) after 15 days of culture. These bioprinted neural tissues expressed TUJ1, (15 ± 1.3%), the dopamine marker, tyrosine hydroxylase (TH) (8 ± 0.6%) and other glial markers such as glial fibrillary acidic protein (GFAP) (15 ± 3.5%) and oligodendrocyte progenitor marker (O4) (4 ± 0.9%) as showed by flow cytometry after 30 days. Also, relative gene expression by quantitative polymerase chain reaction (qPCR) showed expression of TUBB3 (TUJ1) and specific midbrain dopaminergic neurons Nuclear receptor related 1 protein (NURR1), LIM Homeobox Transcription Factor 1 Beta (LMX1B), TH, and Paired Box 6 (PAX6) in these tissues after 30 days. In conclusion, we have demonstrated that 3D bioprinting pluripotent stem cell derived neural tissues using a microsphere-laden bioink can promote the differentiation of neural tissue when used to bioprint hiPSC-derived NPCs.